PENGUKURAN DAN ANALISIS KECEPATAN REAKSI TERHADAP PERUBAHAN WARNA DAN BUNYI SEBAGAI DASAR DALAM PERANCANGAN ALAT PENGENDALI ERGONOMIS - I Wayan Sukania; Lamto Widodo; Jennifer Juyanto; Yovita NG (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2023)
Reaction time is the time span between receiving a stimulus and the initial appearance of a person's response. Many work equipment requires a quick reaction from the operator on the signal displayed. The quick reaction is turning off the engine, pressing the emergency button, braking etc. Quick action is needed, among others, to prevent work accidents, prevent damage to equipment. To find out the characteristics of the speed of reaction to several types of stimuli, a series of experiments was carried out. The study was conducted under normal conditions on 47 respondents in the ergonomics laboratory. Stimulation given changes in color and sound as well as visual cues in the form of moving needles. The calculation results show that the speed of reaction is influenced by the type of stimulus. The highest reaction speed occurs when the stimulus is in the form of a moving pointer, followed by the yellow, green, red buttons, the sound of the alarm and finally the whirring sound. The control board prototype designed using reaction speed characteristic data is equipped with 3 color push buttons that correspond to the color of the indicator light, 1 yellow push button to respond to a whirring sound indicator and an emergency stop button to respond to an alarm sound and a step on by foot switch to respond to indicators moving pointer emergency stop button to respond to the alarm sound as well as a step-by-foot switch to respond to indicators in the form of a moving pointer.